A comparison of Jason-2 plasmasphere electron content measurements with ground-based measurements - A. J. Mazzella Jr.; E. Yizengaw (Annales Geophysicae, 2023)
Previous studies utilizing the Global Positioning System (GPS) receivers aboard Jason satellites have performed measurements of plasmasphere electron content (PEC) by determining the total electron content (TEC) above these satellites, which are at altitudes of about 1340 km. This study uses similar methods to determine PEC for the Jason-2 receiver for 24 July 2011. These PEC values are compared to previous determinations of PEC from a chain of ground-based GPS receivers in Africa using the SCORPION method, with a nominal ionosphere–plasmasphere boundary at 1000 km. The Jason-2 PECs with elevations greater than 60∘ were converted to equivalent vertical PEC and compared to SCORPION vertical PEC determinations. In addition, slant (off-vertical) PECs from Jason-2 were compared to a small set of nearly co-aligned ground-based slant PECs. The latter comparison avoids any conversion of Jason-2 slant PEC to equivalent vertical PEC, and it can be considered a more representative comparison. The mean difference between the vertical PEC (ground-based minus Jason-2 measurements) values is 0.82 ± 0.28 TEC units (1 TEC unit=1016 electrons m−2). Similarly, the mean difference between slant PEC values is 0.168 ± 0.924 TEC units. The Jason-2 slant PEC comparison method may provide a reliable determination for the plasmasphere baseline value for the ground-based receivers, especially if the ground stations are confined to only midlatitude or low-latitude regions, which can be affected by a non-negligible PEC baseline.